US Patent No. US 7,698,954 B2: Multiphase coriolis meter - Tombs, M; Henry, M; Duta, MD; Langansan, R; Dutton, R; Mattar, WM (United States Patent and Trademark Office, 2010)
A flowmeter is disclosed. The flowmeter includes a vibratable flowtube, and a driver connected to the flowtube that is operable to impart motion to the flowtube. A sensor is connected to the flowtube and is operable to sense the motion of the flowtube and generate a sensor signal. A controller is connected to receive the sensor signal. The controller is operable to determine an individual flow rate of each phase within a multi-phase flow through the flowtube.